2020
DOI: 10.3390/biomimetics5010008
|View full text |Cite
|
Sign up to set email alerts
|

Using a Convolutional Siamese Network for Image-Based Plant Species Identification with Small Datasets

Abstract: The application of deep learning techniques may prove difficult when datasets are small. Recently, techniques such as one-shot learning, few-shot learning, and Siamese networks have been proposed to address this problem. In this paper, we propose the use a convolutional Siamese network (CSN) that learns a similarity metric that discriminates between plant species based on images of leaves. Once the CSN has learned the similarity function, its discriminatory power is generalized to classify not just new picture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…We chose Euclidean distance [22][23][24] as our distance metric. Take one of the small datasets for example, the number .…”
Section: Design Choicementioning
confidence: 99%
“…We chose Euclidean distance [22][23][24] as our distance metric. Take one of the small datasets for example, the number .…”
Section: Design Choicementioning
confidence: 99%
“…latest advances presented e.g. in Figueroa‐Mata and Mata‐Montero 2020, Villon et al 2020), or by more strongly considering additional information e.g. of geographical locations as suggested for instance by Wittich et al (2018) or using other ancillary information (Goldsmith et al 2016, Terry et al 2020), e.g.…”
Section: Discussionmentioning
confidence: 99%
“…For comparison, FSL techniques based on metric-learning were also implemented. A convolutional Siamese neural network was developed to find the relationship between two comparable classes [37]. Recently, researchers have reported that Siamese networks perform well in complicated FSL tasks with shared weights of the backbone CNN model [16].…”
Section: Other Types Of Few-shot Learningmentioning
confidence: 99%